Modelowanie modularne w ujęciu dynamiki systemowej - Łatuszyńska, Małgorzata (Modular Modelling in System Dynamics Approach, 2005)
The paper presents the direction of System Dynamics methodology development called modular modelling. It is described the idea of modular modelling and the example of System Dynamics model constructed on the basis of predefined modules.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 42-49